Data driven decision-making for older patients with hepatocellular carcinoma. (March 2021) - Shapey, Iestyn M.; Malik, Hassan Z.; de Liguori Carino, Nicola
Abstract: Older age is a risk factor for the development of HCC. However, the treatment options available for older patients with HCC, their safety, efficacy and utility, are poorly understood resulting in challenging decision-making. In this review, we aim to report the best available evidence to facilitate optimal decision making for older patients with HCC. We report that surgical resection for HCC is equally safe (90-day mortality ~3%) and effective (five-year disease free survival ~40%) for older patients as it is for younger patients. Five-year survival after ablation therapy for HCC is in excess of 50% in older patients, whilst morbidity rates are in the region of 3%. Survival rates of 30% after chemoembolisation reflects its role as a non-curative treatment. Transplantation is an option that may be helpful for a minority of patients, but the high risks of in-hospital mortality and lower likelihood of receiving a transplant should be duly considered before committing to this approach. We therefore advocate an individualised assessment for older patients based on these risk profiles and probabilities of optimal outcomes. In patients with a projected life-span ≥ 3 years, and who have sufficient physiological and functional reserve, surgical resection should be the treatment of choice. Patients with a projected life-span < 3 years are better served with loco-regional therapies, and tumour size, at a threshold of 3 cm, should guide the choice between ablation and chemoembolisation therapies.